Overview on proposed Muslim elderly enrichment centre, Shah Alam - Azman, Tahirah Zahirah; Abdul Rahim, Asiah; Salleh, Nurul Hamiruddin (2015)
The statistic shows that Malaysia is becoming an ageing nation by 2030. This indicates the demand of care and facilities to support the wellbeing of elderly. Statistics shows that more and more elderly in Malaysia are falling into psychological health problems such as depression and Dementia-Alzheimer due in part to the lack of simulation, meaningful activities and experiences. This paper describes ideas on conducive environment, activities, and needs of Muslim elderly in activity centre. This paper will provide complete guidelines for elderly facilities and amenities to enhance quality of life and maximize their cognitive and physical ability according to Islamic way. Islamic in this respect is designed in term of creating the Islamic environment as well as consideration on Muslim activities and prophets Sunnah such as swimming and archery. The parameters of the study are the naturally mapped environment and therapeutic activities as it help in non- pharmacological Alzheimer‟s treatment. Method to collect data will be through literature review, case and precedent studies, as well as interviews. The findings of the research lead to several suggestions in order to prepare an appropriate proposal in building an elderly enrichment centre. The end product of this design thesis will include spatial planning involving cognitive and life enhancing environment for elderly. The space will involve detailing of environment indicator. Healing architecture will be used utilizing colour, form and lighting. Indoor and outdoor spaces and activity to encourage interaction and spiritual development as well as open and friendly spaces will be provided.